FIGURATIVE LANGUAGE USED IN SAUDI NEWS HEADLINES RELATED TO CORONAVIRUS (COVID-19) - Fadi Maher Al-Khasawneh (Universitas Islam Sumatera Utara (UISU), 2021)
Figurative language is a part of Stylistics and there was much research on how figurative language was used in different contexts. The present research aimed at analyzing the figurative language used in Saudi news headlines related to Coronavirus (COVID-19). A descriptive qualitative research design was used in this study. The data source of this study was the Saudi Press Agency (SPA), and the data were headlines related to Coronavirus (COVID-19) published from the period from February 15 to March 31, 2020. The obtained data from this study were organized, classified, and coded. The findings of this study revealed that there were seven speech figures used in this study ( personification, hyperbole, understatement, paradox, synecdoche, apostrophe, and metonymy). The most used speech figure was personification and the least used one was metonymy. Each type of these speech figures had its own function such as to expand meaning, create intense emotions, and express a lot in a limited space. The researcher provides some recommendations for future research work in order to get more insights and contributions to this topic.